Composite ion exchange membrane and preparation and application thereof
By using a composite ion exchange membrane in a flow battery, which consists of an ion exchange membrane and a 3,4-dimethylpyrrole polymer layer, the problem of insufficient conductivity and ion selectivity in existing batteries is solved, and the efficient and stable operation of the battery is achieved and the cost reduction of the battery is achieved.
Patent Information
- Application Number
- CN202411851262.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-28
AI Technical Summary
In existing flow batteries, the conductivity and ion selectivity of the ion conductive film are insufficient, which limits the efficient and stable operation of the battery and the cost reduction.
A composite ion exchange membrane is used, which consists of an ion exchange membrane and a 3,4-dimethylpyrrole polymer layer coupled to the ion exchange membrane, and the conductive properties and ion selectivity of the membrane are improved by a specific preparation method.
It significantly improves the electrical performance of the flow battery, allowing the battery to operate efficiently and stably, while reducing costs.
Smart Images

Figure CN119725594A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an ion exchange membrane and a preparation method thereof, in particular to a composite ion exchange membrane and a preparation method thereof and an application thereof in a liquid flow battery. Background Art
[0002] In the core structure of flow batteries, the ion conduction membrane plays a vital role. It is not only a barrier to prevent the mutual penetration of vanadium ions in the positive and negative electrolytes, but also a key channel for the circulation of hydrogen ions to form a closed loop of the battery. The performance of the ion conduction membrane directly determines the overall performance of the entire battery system. An ideal ion conduction membrane should have high ion selectivity, excellent ion conduction efficiency, excellent chemical stability and economically reasonable cost.
[0003] At present, the mainstream commercial membrane material in the field of liquid flow batteries is perfluorosulfonic acid ion conductive membrane (Nafion). Although it has stable performance, its ion selectivity is insufficient and its cost is high, which limits its widespread application in the industrial field. In contrast, non-fluorine ion conductive membranes have the advantages of low cost, high thermal stability and mechanical strength, and good ion selectivity. This type of membrane material achieves effective separation of conductive ions and protons through a fine pore size screening mechanism and charge repulsion effect. However, its relatively low conductivity is still a key obstacle to its further commercialization. Therefore, the current research focus is on the development of an ion conductive membrane that has both high conductivity and excellent vanadium ion barrier properties. It aims to ensure the efficient and stable operation of liquid flow batteries, while further reducing costs and promoting the expansion of all-vanadium liquid flow battery energy storage technology to a broader market. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a composite ion exchange membrane with excellent electrical conductivity and ion selectivity. Another purpose of the present invention is to propose a method for preparing a composite ion exchange membrane to solve the problem of how to obtain a composite ion exchange membrane. The third purpose of the present invention is to apply the composite ion exchange membrane to the preparation of a liquid flow battery to solve the problem of how to improve the electrical performance of the liquid flow battery.
[0005] Technical solution: The composite ion exchange membrane described in the present invention comprises an ion exchange membrane and a 3,4-dimethylpyrrole polymer layer coupled to the ion exchange membrane.
[0006] Preferably, the ion exchange membrane comprises a perfluorosulfonic acid ion exchange membrane and a non-fluorosulfonic acid ion exchange membrane.
[0007] The second aspect of the present invention discloses a method for preparing the composite ion exchange membrane, comprising the following steps:
[0008] (1) dissolving a silane coupling agent in an alcohol solvent, adding an organic acid, and stirring to react to obtain a first solution;
[0009] (2) immersing the ion exchange membrane in the first solution, heating the solution for reaction, adding an alkali solution for neutralization, and taking out the membrane to obtain a modified base membrane;
[0010] (3) The modified base membrane is immersed in an oxidant aqueous solution, and then a 3,4-dimethylpyrrole aqueous solution is added dropwise in an ice-salt bath. After the polymerization reaction, the membrane is taken out, washed, and dried to obtain a composite ion exchange membrane.
[0011] The 3,4-dimethylpyrrole monomer is polymerized by oxidative coupling to form a polymer layer. The polymer layer containing methyl substituents not only improves the conductivity of the ion membrane, but also improves the energy efficiency of the membrane by increasing the voltage efficiency of the membrane, thereby achieving the effect of improving the application performance of the membrane.
[0012] Preferably, in step (1), the alcohol solvent includes at least one of methanol, ethanol, propanol and butanol, the organic acid includes at least one of formic acid, acetic acid, propionic acid and benzoic acid, and the silane coupling agent includes at least one of vinyltrimethoxysilane, vinyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane.
[0013] Preferably, in step (1), the concentration of the silane coupling agent in the first solution is 4.0-8.0 wt %, an organic acid is added until the pH of the first solution is 2.0-4.0, and the stirring reaction conditions are stirring the hydrolysis reaction at room temperature for 0.5-1 h.
[0014] Preferably, in step (2), the heating reaction conditions are heating to 50-90° C., reacting at a constant temperature for 1-5 hours and then standing for 12-36 hours.
[0015] Preferably, in step (3), the oxidant comprises at least one of ammonium persulfate, potassium persulfate, potassium iodate, potassium dichromate, potassium permanganate, hydrogen peroxide, and ferric chloride, and the concentration of the oxidant aqueous solution is 0.5-1.5 mol / L.
[0016] Preferably, in step (3), the concentration of the 3,4-dimethylpyrrole aqueous solution is 4.0-8.0%wt, the temperature of the ice-salt bath is 0-10°C, and the molar ratio of the 3,4-dimethylpyrrole to the oxidant is 1.5-2.0:1.0.
[0017] Preferably, in step (3), the polymerization reaction is carried out under stirring for 0.5-2 hours, and the washing method is to wash the surface of the membrane with ether and distilled water in sequence.
[0018] The third aspect of the present invention discloses the application of the composite ion exchange membrane in a liquid flow battery.
[0019] In some embodiments, the flow battery comprises one of an all-vanadium flow battery, a zinc / bromine flow battery, a zinc / iodine flow battery, an iron / chromium flow battery, or a vanadium / bromine flow battery.
[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0021] The composite ion exchange membrane prepared in the present invention has excellent electrical conductivity and ion selectivity, and each performance is better than the existing Nafion membrane. The liquid flow battery constructed by the present invention has good electrical performance, and the present invention can enable the liquid flow battery to operate efficiently and stably. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a microscopic morphology diagram of the composite ion exchange membrane of the present invention. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0024] Example 1: A composite ion exchange membrane, such as Figure 1 As shown, it comprises an ion exchange membrane and a 3,4-dimethylpyrrole polymer layer coupled to the ion exchange membrane.
[0025] The preparation method of the composite ion exchange membrane is as follows:
[0026] (1) dissolving γ-methacryloxypropyltrimethoxysilane in ethanol at a final concentration of 5.0 wt %, adding acetic acid until the pH value is 3.0, and performing a hydrolysis reaction at room temperature with stirring for 1 h to obtain a first solution;
[0027] (2) immersing the perfluorosulfonic acid ion exchange membrane Nafion117 in the first solution, heating to 60° C., reacting at a constant temperature for 1 hour, standing for 24 hours, and then adding a sodium hydroxide aqueous solution to neutralize to neutrality, and taking out the membrane to obtain a modified base membrane;
[0028] (3) The modified base membrane is immersed in 1L of water, 1 mol of ferric chloride hexahydrate is added and stirred until dissolved, and then a 5wt% aqueous solution of 3,4-dimethylpyrrole is added dropwise in an ice-salt bath at 0°C, wherein the molar ratio of 3,4-dimethylpyrrole to ferric chloride is 1.5. After the polymerization reaction is carried out under stirring for 0.5h, the membrane is taken out, and the surface of the membrane is cleaned with ether and distilled water in turn, and a composite ion exchange membrane is obtained after drying.
[0029] Example 2: A method for preparing a composite ion exchange membrane is as follows:
[0030] (1) dissolving γ-aminopropyltriethoxysilane in methanol at a final concentration of 8.0 wt %, adding benzoic acid to a pH of 4.0, and stirring at room temperature for a hydrolysis reaction for 0.5 h to obtain a first solution;
[0031] (2) immersing the perfluorosulfonic acid ion exchange membrane in the first solution, heating to 50° C., reacting at a constant temperature for 5 hours, standing for 12 hours, and then adding a sodium hydroxide aqueous solution to neutralize to neutrality, and taking out the membrane to obtain a modified base membrane;
[0032] (3) The modified base membrane is immersed in a potassium iodate aqueous solution with a concentration of 0.5 mol / L, and then a 3,4-dimethylpyrrole aqueous solution with a concentration of 8.0 wt% is added dropwise in an ice-salt bath at 4°C, wherein the molar ratio of 3,4-dimethylpyrrole to potassium iodate is 2.0. After the polymerization reaction is carried out under stirring for 2 hours, the membrane is taken out, and the surface of the membrane is cleaned with ether and distilled water in turn, and then dried to obtain a composite ion exchange membrane.
[0033] Example 3: A method for preparing a composite ion exchange membrane is as follows:
[0034] (1) dissolving γ-aminopropyltrimethoxysilane in isopropanol at a final concentration of 4 wt %, adding formic acid to a pH of 2.0, and stirring at room temperature for a hydrolysis reaction for 1 h to obtain a first solution;
[0035] (2) immersing the perfluorosulfonic acid ion exchange membrane in the first solution, heating to 90° C., reacting at a constant temperature for 1 hour, standing for 36 hours, adding a sodium hydroxide aqueous solution to neutralize to neutrality, and taking out the membrane to obtain a modified base membrane;
[0036] (3) The modified base membrane is immersed in a 1.5 mol / L ferric chloride aqueous solution, and then a 6.5 wt% 3,4-dimethylpyrrole aqueous solution is added dropwise in an ice-salt bath at 10°C, wherein the molar ratio of 3,4-dimethylpyrrole to ferric chloride is 1.7:1. After the polymerization reaction is carried out under stirring for 1 hour, the membrane is taken out, and the surface of the membrane is cleaned with ether and distilled water in turn, and then dried to obtain a composite ion exchange membrane.
[0037] Example 4: A method for preparing a composite ion exchange membrane is as follows:
[0038] (1) dissolving γ-methacryloxypropyltrimethoxysilane in n-butanol at a final concentration of 6 wt %, adding propionic acid to a pH of 3.0, and stirring at room temperature for a hydrolysis reaction for 0.5 h to obtain a first solution;
[0039] (2) immersing the non-fluorinated sulfonic acid ion exchange membrane in the first solution, heating to 70° C., reacting at a constant temperature for 3 hours, standing for 24 hours, adding alkaline solution for neutralization, and taking out the membrane to obtain a modified base membrane;
[0040] (3) The modified base membrane is immersed in a 1.0 mol / L ferric chloride aqueous solution, and then a 7 wt % 3,4-dimethylpyrrole aqueous solution is added dropwise in an ice-salt bath at 0°C, wherein the molar ratio of 3,4-dimethylpyrrole to ferric chloride is 1.8. After the polymerization reaction is carried out under stirring for 1.5 h, the membrane is taken out, and the surface of the membrane is cleaned with ether and distilled water in turn, and then dried to obtain a composite ion exchange membrane.
[0041] Comparative Example 1: The rest is the same as Example 1, except that:
[0042] The 3,4-dimethylpyrrole in step (3) was replaced by pyrrole.
[0043] Comparative Example 2: The rest is the same as Example 1, except that:
[0044] The 3,4-dimethylpyrrole in step (3) was replaced by 3-methylpyrrole.
[0045] Comparative Example 3: The rest is the same as Example 1, except that:
[0046] The 3,4-dimethylpyrrole in step (3) was replaced by 3-hydroxypyrrole.
[0047] Comparative Example 4: The rest is the same as Example 1, except that:
[0048] The γ-methacryloxypropyltrimethoxysilane in step (1) was replaced with vinyltrimethoxysilane.
[0049] Comparative Example 5: The rest is the same as Example 1, except that:
[0050] The ferric chloride in step (3) is replaced by hydrogen peroxide.
[0051] Comparative Example 6: The rest is the same as Example 1, except that:
[0052] The ferric chloride in step (3) is replaced by ammonium persulfate.
[0053] Comparative Example 7: The rest is the same as Example 1, except that:
[0054] The ferric chloride in step (3) is replaced by potassium dichromate.
[0055] Comparative Example 8: The rest is the same as Example 1, except that:
[0056] The ferric chloride in step (3) is replaced by potassium permanganate.
[0057] Comparative Example 9: The rest is the same as Example 1, except that:
[0058] The acetic acid in step (1) is replaced by hydrochloric acid.
[0059] Comparative Example 10: The rest is the same as Example 1, except that:
[0060] The acetic acid in step (1) was replaced by oxalic acid.
[0061] The conductivity and ion selectivity of the composite ion exchange membranes prepared in Examples 1-4 and Comparative Examples 1-10 were measured, and all-vanadium liquid flow batteries were assembled using these composite ion exchange membranes to measure the electrical properties of the batteries. The results are as follows:
[0062] The actual application performance of the membrane is characterized by the performance of a single cell. The test cell is composed of an ion membrane, a carbon felt electrode and other current collectors, and the electrolyte circulates through a magnetic pump.
[0063] Table 1 Test results of conductivity, ion selectivity and flow battery electrical performance of different composite ion exchange membranes
[0064]
[0065]
[0066] As can be seen from the results in Table 1, after replacing the polymerized monomers in Comparative Examples 1-3, the various properties of the composite membrane and the electrical properties of the assembled battery are significantly reduced compared with Example 1, and the various values are all lower than the initial base membrane (i.e., the untreated perfluorosulfonic acid ion exchange membrane). Therefore, among many pyrroles and their derivatives, only the polymer layer formed by 3,4-dimethylpyrrole can significantly improve the various properties of the base membrane, and the polymer layer formed by other derivatives not only cannot significantly improve the performance of the base membrane, but even greatly reduces the performance of the base membrane. Comparative Examples 4-8 show that appropriate silane coupling agents and oxidants are more important for the formation of polymer layers. Coupling agents with improper functional group selection and oxidants with excessively strong oxidizing effects cannot form polymer layers with excellent performance, resulting in a significant reduction in the overall performance of the composite membrane, which is not suitable for the improvement of liquid flow battery performance. Comparative Examples 9 and 10 show that although the strongly acidic alcohol solution can effectively dissolve the silane coupling agent, it is not conducive to the in-situ polymerization of 3,4-dimethylpyrrole to form a polymer layer, resulting in a significant reduction in the various properties of the composite membrane compared with Example 1. The present invention uses 3,4-dimethylpyrrole as a monomer and utilizes appropriate silane coupling agents and oxidants to prepare a polymer layer that can significantly improve various properties of the base membrane, so that the composite membrane prepared by the present invention can significantly improve the electrical properties of the liquid flow battery and has good application prospects.
Claims
1. A composite ion exchange membrane, characterized in that: The invention comprises an ion exchange membrane and a 3,4-dimethylpyrrole polymer layer coupled to the ion exchange membrane.
2. The composite ion exchange membrane according to claim 1, characterized in that: The ion exchange membrane includes a perfluorosulfonic acid ion exchange membrane and a non-fluorosulfonic acid ion exchange membrane.
3. The method for preparing a composite ion exchange membrane according to claim 1 or 2, characterized in that: The steps include: (1) dissolving a silane coupling agent in an alcohol solvent, adding an organic acid, and stirring to react to obtain a first solution; (2) immersing the ion exchange membrane in the first solution, heating the solution for reaction, adding an alkali solution for neutralization, and taking out the membrane to obtain a modified base membrane; (3) The modified base membrane is immersed in an oxidant aqueous solution, and then a 3,4-dimethylpyrrole aqueous solution is added dropwise in an ice-salt bath. After the polymerization reaction, the membrane is taken out, washed, and dried to obtain a composite ion exchange membrane.
4. The method for preparing a composite ion exchange membrane according to claim 3, characterized in that: In step (1), the alcohol solvent includes at least one of methanol, ethanol, propanol, and butanol, the organic acid includes at least one of formic acid, acetic acid, propionic acid, and benzoic acid, and the silane coupling agent includes at least one of vinyltrimethoxysilane, vinyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and γ-methacryloxypropyltrimethoxysilane.
5. The method for preparing the composite ion exchange membrane according to claim 3, characterized in that: In step (1), the concentration of the silane coupling agent in the first solution is 4.0-8.0 wt %, and an organic acid is added until the pH of the first solution is 2.0-4.
0. The stirring reaction conditions are stirring the hydrolysis reaction at room temperature for 0.5-1 h.
6. The method for preparing a composite ion exchange membrane according to claim 3, characterized in that: In step (2), the heating reaction conditions are heating to 50-90°C, reacting at a constant temperature for 1-5 hours and then standing for 12-36 hours.
7. The method for preparing a composite ion exchange membrane according to claim 3, characterized in that: In step (3), the oxidant includes at least one of ammonium persulfate, potassium persulfate, potassium iodate, potassium dichromate, potassium permanganate, hydrogen peroxide, and ferric chloride.
8. The method for preparing a composite ion exchange membrane according to claim 3, characterized in that: In step (3), the concentration of the 3,4-dimethylpyrrole aqueous solution is 4.0-8.0%wt, the temperature of the ice-salt bath is 0-10°C, and the molar ratio of the 3,4-dimethylpyrrole to the oxidant is 1.5-2.0:1.
0.
9. The method for preparing a composite ion exchange membrane according to claim 3, characterized in that: In step (3), the polymerization reaction is carried out under stirring for 0.5-2 hours, and the washing method is to wash the surface of the membrane with ether and distilled water in sequence.
10. Use of the composite ion exchange membrane according to claim 1 or 2 in a liquid flow battery.